PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA GURU - Siti Sulistyaningsih W., Suprihatmi SW. & (Universitas Slamet Riyadi, 2006)
ABSTRACT The research is designed and aimed to know (1). The leadership performance and work atmosphere partially and simultaneously to teacher’s performance motivation. (2). Variables which have more influences to teacher’s motivation. Population of 60 person taken in such research in the teacher of SMA Muhammadiyah 1 Surakarta, the sample drawn is 30 teachers using proportional cluster random sampling teacher’s. the instrument used are questionnaire. Data is analyzed using double linear regression analysis, Z and F analyzing and also R2 one. From the data analyzed, it is formulated in equation of double linear regression, at follows:Y= 1,803 + 0,668 x1 + 0,280 x2. the result of Z aromatic 4,794 and 2,678 shows that the leadership performance work atmosphere that they have positive and significant, both partially and simultaneously to teacher’s performance motivation. The result of F aromatic of 18,217 within 0,000 significant grade/level means that the leadership performance and work atmosphere simultaneously have positive significant influence to teacher’s performance motivation.R2 = 0,543 shows that leadership performance and work atmosphere contributes 54,3% to teacher’s performance motivation while the other factors contributes 45,7%. Since the result regression coefficient b1 > b2 or 0,668 > 0,280, the variable of leadership performance has more dominant influence to teacher’s performance motivation. The whole hypothesis presented shows the valid or accurate result. Keywords:style leadership, environmental of job, teacher job motivation.